Determination of Diphenylamine in Gunshot Residue by HPLC-MS/MS - Hongcheng Mei; Yangke Quan; Wenhao Wang; Hong Zhou; Zhanfang Liu; Huixia Shi; Peng Wang (Wolters Kluwer Medknow Publications, 2016)
A high performance liquid chromatography tandem mass spectrometry/mass spectrometry (HPLC-MS/MS) protocol was developed for the determination of diphenylamine (DPA). Four productions of DPA were selected for qualitative assay and the peak area of the main product ion for quantitation. By means of separation using an Agilent Extend-C18 column (CA, USA) (150 mm × 4.6 mm, 5 μm) with methanol-water (90:10) as the mobile phase, DPA was detected by electrospray ionization (ESI) tandem mass spectrometry in positive mode. The linearity of the peak area versus concentration ranged 5-500 ng/mL, r 2 = 0.9978. The limit of detection (S/N =3) of this method was 0.3 ng/mL. This method is applicable for the determination of DPA in gunshot residue.